HEGEL’S CONCEPT OF NOTRECHT - Jevtić, Nevena (Glasnik Advokatske komore Vojvodine, 2020)
This paper explores significance of right of necessity (Notrecht) in Hegel’s philosophy of right. First part of the paper will draw basic motives of Hegel’s abstract category of ownership, and Hegel’s quarrel with Savigny which represents a fundamental historical and philosophical framework of this right. The second part will give an overview of Kant’s and Fichte’s manner of understanding and definition f right of necessity within his practical philosophy. As a key characteristic that differentiate Hegel’s notion of right of necessity from those of his predecessor, a social-political dimension will be underlined as a topic of analysis in the third part of the paper.
Keywords: Philosophy of Right, Notrecht, Property, Necessity, Bourgeois Society, Hegel